2016
DOI: 10.1038/srep28206
|View full text |Cite
|
Sign up to set email alerts
|

Ferromagnetic resonance induced large microwave magnetodielectric effect in cerium doped Y3Fe5O12 ferrites

Abstract: In recent years, multifunctional materials contained simultaneous ferroelectric and ferromagnetic ordering have been realized. Here, a real time room temperature adaptive materials system, which demonstrates an RF magnetodielectric (MD) response, i.e., CexY3−xFe5O12 (x = 0, 0.05, 0.1, 0.15, 0.2), is reported. The magnetic and dielectric properties of Ce-doped YIG microwave ferrites processed by a traditional ceramic route have been measured over a frequency range of 4–8 GHz (C-band). The substitution of Ce not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 44 publications
(49 reference statements)
2
16
0
Order By: Relevance
“…(907.6 eV) and Ce 4+ 3d3/2 (918.0 eV) have also been recognized within the sample [51,52]. The analysis for the Co 2p spectrum in the sample becomes much more complicated due to the coexistence of intensive Ba 3d spectrum within the same range of binding energies (780 to 795 eV).…”
Section: Influence Of Cerium Content On Catalytic Activitymentioning
confidence: 87%
“…(907.6 eV) and Ce 4+ 3d3/2 (918.0 eV) have also been recognized within the sample [51,52]. The analysis for the Co 2p spectrum in the sample becomes much more complicated due to the coexistence of intensive Ba 3d spectrum within the same range of binding energies (780 to 795 eV).…”
Section: Influence Of Cerium Content On Catalytic Activitymentioning
confidence: 87%
“…Such materials are mainly composites of complex oxides of transition metals 6 . Since the microwave properties of a material are determined not only by the dielectric contribution, but also by the magnetic one, the use of magnetodielectrics is the most suitable solution to the problem 7 . Ferrites are the most typical representatives of complex transition metal oxides with optimal magnetodielectric properties 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Cerium (Ce) element has amazing quality as it can be effortlessly exchangeable between 4+ valence state and 3+ valence state [66]. Also, cerium substituted yttrium iron oxide attracted much attention due to their remarkable multiferroic (MF) properties such as magnetodielectric (MD) and strong magneto-optical (MO) effects [67][68][69]. Soumah, Lucile, et al, demonstrated that Bismuth substituted Yttrium iron oxide (Bi:YIG) leads to extremely-low Gilbert damping together with perpendicular magnetic anisotropy (PMA) [70].…”
Section: Introductionmentioning
confidence: 99%